ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK MANDIRI KONVENSIONAL DAN BANK MANDIRI SYARIAH - Atik Nurwahyuni; Dibyo Iskandar; Yenni Khristiana (STIE AUB Surakarta, 2018)
This study aims to determine the differences in the financial performance of conventional Bank Mandiri with syariah Mandiri banks measured using the ratio of Loan deposit ratio, operational cost of operating income, Non performing loan, Return on asset, Return on equity.The population of this study is the conventional Banking Mandiri financial report and sharia Mandiri banking period 2009-2016 period listed in Indonesia Stock Exchange. The sampling method uses a census or saturated sempel technique. The analytical technique used the data normality test and the independent test independent of t-test sample. This research is a quantitative research. Sources of research data is secondary data in the form of conventional Mandiri banking quarterly financial report and syariah Mandiri banking. The final result of this study proves that the ratio of BOPO, NPL, ROE of conventional Bank Mandiri and Bank Mandiri sharia there is a significant difference. While the ratio of LDR and ROA of conventional Bank Mandiri and Bank Mandiri sharia there is no significant difference.Keywords: Banking Mandiri, Financial performance, LDR, BOPO, NPL, ROA, ROE